Genetic prion disease – fatal familial insomnia (clinical case) - T. V. Sorokovikova; A. M. Morozov; A. N. Kryukova; S. A. Naumova; A. V. Mitropolskaya (Acta Biomedica Scientifica, 2024)
Background. Fatal familial insomnia is a rare genetically determined neurodegenerative disorder from the group of prion diseases. Its main cause is the autosomal dominant D178N mutation of the PRNP gene, which leads to the synthesis of the pathological prion protein PrP.The aim. Using the example of a clinical case to describe an example of the early onset of fatal familial insomnia in a teenager, a clinical example of its management.Materials and methods. Female patient V., 16 years old, of hyposthenic constitution, undernourished, with negative family history (multiple sclerosis in her paternal grandmother) for the first time consulted a neurologist in Tver for the complaints of superficial sleep, shortened to 4–5 hours, unspecific pain all over the body, periodic numbness in the upper limbs. Six months later, retardation of speech and movements, changes in gait, and intentional tremor occurred; sleep was shortened to 2 hours. In the future, the teenager lost the ability to independently maintain the vertical body position, the ability to walk without assistance, speech was reduced to syllable answers to questions. In order to verify the diagnosis and to carry out differential diagnosis with other neurodegenerative diseases, the girl underwent auxiliary research methods: detection of antibodies to nuclear antigens, magnetic resonance imaging, computer electroencephalography, polyexomal genome sequencing.Results. Based on the anamnesis, complaints, clinical picture and results of genetic research the final diagnosis of fatal familial insomnia was made. Due to the lack of etiological and pathogenetic therapy, the patient was subsequently provided with palliative medical care. The fatal outcome occurred 19 months after the onset of the disease.Conclusions. The presented clinical case reflects the complexity of managing patients with rare genetic diseases, confirms the need for mandatory polyexomal genome sequencing in order to verify the diagnosis, which allows timely palliative care